(untitled) (Academicia Globe: Inderscience Research, 2021)
In this article, there were studied innovation management and coordination of the system or training pedagogical staff, especially the world experience of applying online education to the above-mentioned system. Besides, there were also described opportunities of economizing on state finance and several other advantages of applying online education for training pedagogical staff working in the Public education system. We will be able to achieve a promising future by improving the flow of the Internet, taking the place of young people in the life of our society.